2018
DOI: 10.1038/mi.2017.93
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of γδ T cells in cigarette smoke and influenza infection

Abstract: Airborne pathogens commonly trigger severe respiratory failure or death in smokers with lung disease. Cigarette smoking compromises the effectiveness of innate immunity against infections but the underlying mechanisms responsible for defective acquired immune responses in smokers remains less clear. We found that mice exposed to chronic cigarette smoke recovered poorly from primary Influenza A pneumonia with reduced type I and II interferons (IFNs) and viral-specific immunoglobulins, but recruited gamma delta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 49 publications
2
45
0
Order By: Relevance
“…To further examine the translational relevance of reduction of M1-associated markers, impaired macrophage responses to poly I:C, and surfactant dysregulation in mice exposed to ENDS vapor, we next assessed defenses against acute viral infection. We have previously shown that mice exposed to chronic cigarette smoke, before sublethal infection with influenza A, fail to mount the appropriate antiviral responses and exhibit increased morbidity (32). In a similar manner, mice were exposed to Air (control), chronic ENDS-vehicle (PG/VG), or ENDS-nicotine for 3 months and were subsequently challenged with the influenza A virus (45 TCID 50 /mouse).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To further examine the translational relevance of reduction of M1-associated markers, impaired macrophage responses to poly I:C, and surfactant dysregulation in mice exposed to ENDS vapor, we next assessed defenses against acute viral infection. We have previously shown that mice exposed to chronic cigarette smoke, before sublethal infection with influenza A, fail to mount the appropriate antiviral responses and exhibit increased morbidity (32). In a similar manner, mice were exposed to Air (control), chronic ENDS-vehicle (PG/VG), or ENDS-nicotine for 3 months and were subsequently challenged with the influenza A virus (45 TCID 50 /mouse).…”
Section: Resultsmentioning
confidence: 99%
“…All chemokine analyses were performed on BAL fluid supernatants using a ProcartaPlex Immunoassay (Thermo Fisher Scientific) for selected chemokines (CCL2, CCL3, CCL4 CCL5, CCL11, CXCL1, and CCL20). For the determination of antibody titers in the influenza study, the aforementioned supernatants were used for IgG-specific ELISAs (Southern Biotechnology) as previously described (32). For pulmonary surfactant-specific ELISAs, specifically SP-D (R&D Systems), BAL fluid was acquired as described above.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations